Development of analytical method and validation for Nadolol in pure and pharmaceutical formulations using UV-spectrophotometry and spectrofluorimetry using Hydrochloric acid - Anton Smith A; Akanksha .; Arun R (Journal of Global Pharma Technology, 2019)
Objective: Development of analytical methods is in need for the estimation of drugs in pure and different pharmaceutical formulations. A simple, sensitive, rapid, accurate, precise and economic Spectrophotometric and Spectrofluorimetric method were developed and validated for Nadolol in pure and Pharmaceutical formulations. Methods: The wave length (λmax) used for the estimation of Nadolol is 267nm by Spectrophotometry, excitation (λEx)-267nm and emission (λEm)-300nm by Spectrofluorimetry. Results: Linear correlation was obtained between absorbance and concentration of Nadolol in the concentration ranges of 20-60µg/ml with R2 value 0.998 by Spectrophotometry and linear correlation was obtained between intensity of fluorescence and concentration of Nadolol in the concentration ranges of 1-5µg/ml with R2value 0.993 by Spectrofluorimetry in 0.1 N HCl. The linearity of the calibration curve was validated by the high values of correlation coefficient of regression. LOD and LOQ values for Nadolol were found to be 3.95µg/ml and 11.99µg/ml by Spectrophotometry and 0.90µg/ml and2.74µg/ml by Spectrofluorimetry. Conclusion: Among the two developed methods Spectrofluorimetric method is highly sensitive than the spectrophotometric method. These methods are simple and suitable for the determination of Nadolol in pure and Pharmaceutical preparations.